2017
DOI: 10.1007/s12291-017-0649-2
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxins: Implications on Health

Abstract: Environmental occurrence of and other fungal spores are hazardous to humans and animals. They cause a broad spectrum of clinical complications. Contamination of aflatoxins in agri-food and feed due to and result in toxicity in humans and animals. Recent advances in aspergillus genomics and aflatoxin management practices are encouraging to tackle the challenges posed by important aspergillus species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
71
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(75 citation statements)
references
References 74 publications
(74 reference statements)
2
71
0
2
Order By: Relevance
“…However, it is of note that the problem is compounded because in Nigeria the use of herbal medicines is common and more common it is to buy them from local markets and shops. Aflatoxicosis can lead to acute primary aflatoxicosis with symptoms including hemorrhage, acute liver damage, edema, digestion problems and death [19]. Following chronic intake of aflatoxin there could be a synergistic action with hepatitis B and other carcinogens to elicit primary liver cancer as contained in the work of [20] who examined the relationship between hepatitis B virus (HBV) infection and biomarkers of aflatoxin exposure in West African children.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is of note that the problem is compounded because in Nigeria the use of herbal medicines is common and more common it is to buy them from local markets and shops. Aflatoxicosis can lead to acute primary aflatoxicosis with symptoms including hemorrhage, acute liver damage, edema, digestion problems and death [19]. Following chronic intake of aflatoxin there could be a synergistic action with hepatitis B and other carcinogens to elicit primary liver cancer as contained in the work of [20] who examined the relationship between hepatitis B virus (HBV) infection and biomarkers of aflatoxin exposure in West African children.…”
Section: Resultsmentioning
confidence: 99%
“…Aflatoxin is the most prevalent mycotoxin synthesised by Aspergillus flavus, Aspergillus parasiticus, and Aspergillus nomius in the ideal temperature and humidity (Morrison et al, 2017). Prolonged storage of the chicken's feed creates a high synthesis of the aflatoxin (Sarma et al, 2017). Aflatoxin induces severe cellular defects and carcinogenesis (Kim et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of aflatoxicosis is not limited to some limited geographical area. The clinical manifestations of aflatoxicosis are lethargy, anorexia, lower growth rate, microbial stress, economic losses and toxicity (Sarma et al, 2017). The aflatoxin found as a residue on the poultry's final product (Denli et al, 2009), and it represents the port of entry of aflatoxin exposure in human (Manafi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Unexpectedly, the results showed that aflatoxin concentrations increased from the best to the worst grade of the grains, suggesting that the grading system relying on visual inspection does not reflect a priori extent of contamination. The relatively high aflatoxin levels recorded in feeds of the regions are of concern to both animal and human health, since they are not only detrimental to livestock but can also be carried-over to human via foods derived from these animals, such as eggs, meat, and milk [162].…”
Section: Feed Contaminationmentioning
confidence: 99%